Development of a multiple-piston hydraulic briquetting press hbp and characterization of newsprint briquettes produced (2023)
Technical complexity, power source, cost, and product value are some challenging considerations in briquetting. Most of the available briquetting options are not sustainable due to these challenges, therefore, improved intermediate technology options requiring low energy consumption, high-energy product and acceptable combustion characteristics to meet these challenges are justified by developing a multiple-piston hydraulic briquetting press (HBP) and characterizing the briquettes produced from Gmelina arborea sawdust and newsprint binder. Materials and Methods: Sorted Gmelina arborea sawdust was mixed with pulped newsprint fibers in 5 ratios 10, 20, 30, 40 and 50%, respectively, to produce briquettes. The briquettes were characterized using American Society for Testing and Materials (ASTM), British Standard (BS), and International Standards Organization (ISO) test procedures to determine briquette characteristics. Results: The machine output capacity was 96 briquettes/hour, with low production cost (NGN40, 000.00). The briquettes produced are structurally stable with dimensions: 15.00 mm internal hole, 80.00 mm external diameter, and 60.00 mm height. Low binder briquettes (90:10% wt/wt) are fragile and brittle, while higher binder briquettes are strong and durable. Binder concentration positively improves the combustion characteristics, while the time spent cooking 1 kg of yam is not significantly different for rice. The briquettes thermal efficiency in stove was significantly affected by binder concentration and stove characteristics. Conclusion: The outcomes of this study including high machine output capacity, briquettes’ stability, luminous flame and reduced smokiness showed positive quality contributions to densification study and hence, suitability for domestic heating.